An analysis of internal determinants of performance in rural social enterprises - Peter Musinguzi; Derek Baker; Renato A. Villano (Cogent Business & Management)
Rural social enterprises are organizations that utilize market-oriented strategies to fulfill social objectives within regional and rural settings, particularly in addressing persistent issues like poverty and inequality. Their performance is inadequately researched in the rural context, particularly in developing countries where their contributions to overcoming intractable challenges are most needed. This study contributes to addressing these research gaps by developing a model for assessing internal critical success factors (CSFs) that influence social enterprise performance, and testing it in an empirical investigation of the influence of selected CSFs – entrepreneurial orientation, social salience and business planning on the performance of rural social enterprises. A survey of 521 Ugandan rural social enterprises provided data which was analysed using structural equation modelling and importance performance map analysis. Results reveal that entrepreneurial orientation and business planning are critical to rural social enterprises’ performance, and that business planning mediates the relationship between entrepreneurial orientation and performance. For practitioners and policymakers, these findings suggest that entrepreneurial orientation, social salience, and business planning are critical to the performance of rural social enterprises. Further, findings support rural social enterprises’ use of their entrepreneurial orientation to improve financial performance while also advocating for and increasing social performance. We advance social entrepreneurship research by employing the CSF concept in conjunction with other frameworks, and by developing and quantitatively validating a concise model consisting of internal CSFs based on measurement scales. We assess the psychometric properties of these scales and analyse their influence on the performance of rural social enterprises. These findings provide direction for rural social enterprise scholars, practitioners, advocates, and policymakers.